La falta de tipificación de la contravención de tránsito por exceso de pasajeros en vehículos particulares y sus repercusiones legales. - Valdes Morocho, Nury Jessenia (2023)
Legal norms have been created to regulate human behavior and live harmoniously in society. Thus, Ecuador, in terms of Traffic, has created, repealed, and reformed the different legal norms according to the need that arises after the development of the country in order to put an end to the different legal loopholes existing in Ecuadorian legislation. Thus, this investigative work intends to make known to the Ecuadorian citizenry the legal and social problem that affects each individual due to the simple fact that the civil rights of both the victims and those allegedly responsible for the crime are not fully protected. Conduct that should be regulated. In the present investigation, a general study and analysis are carried out on the effects caused by the fact of not regulating the excess of passengers in private vehicles. The background is investigated because, since the beginning of the creation of the norm that regulates Traffic, transportation, and road safety, have been excluded. In the same way, Comparative Law is taken into consideration, the protected legal right is studied, and above all, it is determined that there is a violation of rights and principles. Among which are the right to physical integrity, legal certainty, road safety, the right to due process, and the principle of legality. An exhaustive investigation has been carried out using the appropriate methodology to collect complete information and obtain a comprehensive analysis. In this way, to propose the solution suggested by the researcher in order to terminate the problem, for which it is necessary that the function of the corresponding state, I reviewed and reformed the Comprehensive Criminal Organic Code, in charge of classifying criminal offenses and establishing the procedure to judge the conduct of the citizen. Keywords: legal vacuum, lack of classification, protected legal right, right to physical integrity, right to due process, the principle of legality.